2000
DOI: 10.1002/chin.200027244
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Monodisperse FePt Nanoparticles and Ferromagnetic FePt Nanocrystal Superlattices.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
496
0
6

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 401 publications
(505 citation statements)
references
References 1 publication
3
496
0
6
Order By: Relevance
“…Antolini et al 55 summarized the ordering effects of PtFe/C alloys reported from several groups. [81][82][83] For example, a PtFe/C alloy prepared by heat treatment at 750 1C and kept under flowing hydrogen for 12-15 h presented an ordered structure, and this ordered catalyst was found to be very stable when exposed to 0.5 M aqueous H 2 SO 4 . An insignificant amount (B0.6 ppm) of Fe was leached out during 16 h of testing, mainly from the free Fe ions present in the alloy.…”
Section: Effects Of Orderingmentioning
confidence: 99%
See 1 more Smart Citation
“…Antolini et al 55 summarized the ordering effects of PtFe/C alloys reported from several groups. [81][82][83] For example, a PtFe/C alloy prepared by heat treatment at 750 1C and kept under flowing hydrogen for 12-15 h presented an ordered structure, and this ordered catalyst was found to be very stable when exposed to 0.5 M aqueous H 2 SO 4 . An insignificant amount (B0.6 ppm) of Fe was leached out during 16 h of testing, mainly from the free Fe ions present in the alloy.…”
Section: Effects Of Orderingmentioning
confidence: 99%
“…Wang et al 28 and Sun 88 synthesized PtFe nanoparticles with various morphologies-spheres, nanowires and nanorods-using simultaneously the reduction of platinum acetylacetonate (Pt(acac) 2 ) and the thermal decomposition of iron pentacarbonyl (Fe(CO) 5 ). 81,89 Synthesis was conducted under reflux in a mixture of oleylamine (OAm) and octadecene (ODE) at 160 1C. Dimensional control of the PtFe nanostructures was achieved by tuning the volume ratio of OAm to ODE.…”
Section: Effects Of Orderingmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] Recent studies indicate that NdFeB, 11 and hexagonal SmCo 12 -based alloy NPs are ideal building blocks for fabricating nanostructured permanent magnet due to strong ferromagnetism observed within their unique structure. However, rare-earth metal-based alloy NPs of SmCo and NdFeB are extremely difficult to prepare and stabilize due to the easy oxidation of Sm(0) and Nd(0) in the alloy structures.…”
Section: Introductionmentioning
confidence: 99%
“…SERS active structures have been fabricated by complex with top-down methods, 4,12,16,17 but wet-chemical synthesis of gold nanoparticles offer potential advantages in simple, high yield, and limited scalable synthesis. 12,18,19,20,21,22 Gold nanostructures, such as nanorods, nanowires, tetrapods, nanoplates and star-shaped particles are particularly attractive for many applications because of their strong confinement of the electromagnetic field and high enhancement that can be tuned over a wide range of optical wave lengths in comparison with ordinary spherical structures. 11,[23][24][25][26][27] Combination of the metal nanostructure with a support material, such as in core-shells, raspberries, and crescents, affords additional advantages in tuning optical properties, improved chemical/mechanical stability, and ease of handling compared to free-standing nanoparticles.…”
Section: Introductionmentioning
confidence: 99%